Development of physical education e-modules for students of the Islamic early childhood education program: utilisation of the FlipHTML5 application - Kuswanto, Cahniyo Wijaya; Pratiwi, Dona Dinda (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: This study addresses the gap in independent learning materials for Early Childhood Islamic Education (PIAUD) students, particularly the absence of physical education modules that integrate teachings from the Quran and Hadith. Research Objectives: The research aims to develop an interactive e-module designed to facilitate independent learning while aligning with Islamic values. Methods: Using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages, the study involved a sample of 50 PIAUD students. Data was collected through observations, interviews, student response questionnaires, and expert validation forms for Islamic and physical education. Both qualitative and quantitative methods were used to assess student engagement, content relevance, ease of use, and the module's overall effectiveness. Findings/Results: The results demonstrated that the e-module significantly improved student engagement and learning outcomes, particularly by integrating Islamic teachings into physical education. Feedback from students and experts confirmed that the module was relevant, user-friendly, and effective in promoting independent learning. Conclusion: The study concludes that the interactive e-modules incorporating Islamic values can enhance independent learning for PIAUD students, and it recommends the development of similar modules for other subjects while advocating for the broader integration of Islamic principles in modern educational tools.